Stable isotopic composition of atmospheric precipitation and natural waters in the vicinity of Barentsburg (Svalbard) - A. A. Skakun; K. B. Chikhachev; A. A. Ekaykin; A. V. Kozachek; D. O. Vladimirova; A. N. Veres; S. R. Verkulich; O. R. Sidorova; N. E. Demidov (Лëд и снег, 2020)
In 2016–2017, during Russian Arctic Expedition on Svalbard (RAE‑S) we have collected the samples of atmospheric precipitation, terrestrial waters, snow and ice on Spitsbergen island in the vicinity of Grønfjorden. The measurements of stable water isotope content (δ18O and δD) in the atmospheric precipitation has allowed to draw the Local Meteoric Water Line (δD = 6,93δ18O − 0,35) and to analyze the relationship between the isotopic content and condensation temperature. Aside from this, the d-excess values in precipitation (dexc= δD − 8δ18O) was interpreted as a marker of the moisture source. It has been demonstrated that the isotopic content of the surface waters (lakes and rivers) clearly points to the dominating type of feeding (atmospheric, ground) of these hydrological objects. We have discovered the interannual variability of the isotopic composition of Lake Kongress water during 2 years and defined the sources of water in its tributes: 13 of them have atmospheric source and 9 – ground source. In general, isotopic content of water in the vicinity of Grønfjorden (mean values are: δ18O = −10,3 ‰, δD = −72,5 ‰) is higher than in other regions of Svalbard.